Ensemble multicolour FRET model enables barcoding at extreme FRET levels - Dagher, Milad; Kleinman, Michael; Ng, Andy; Juncker, David (Nature nanotechnology, 2018)
Quantitative models of Förster resonance energy transfer (FRET)—pioneered by Förster—define our understanding of FRET and underpin its widespread use. However, multicolour FRET (mFRET), which arises between multiple, stochastically distributed fluorophores, lacks a mechanistic model and remains intractable. mFRET notably arises in fluorescently barcoded microparticles, resulting in a complex, non-orthogonal fluorescence response that impedes their encoding and decoding. Here, we introduce an ensemble mFRET (emFRET) model, and apply it to guide barcoding into regimes with extreme FRET. We further introduce a facile, proportional multicolour labelling method using oligonucleotides as homogeneous linkers. A total of 580 barcodes were rapidly designed and validated using four dyes—with FRET efficiencies reaching 76%—and used for multiplexed immunoassays with cytometric readout and fully automated decoding. The emFRET model helps to expand the barcoding capacity of barcoded microparticles using common organic dyes and will benefit other applications subject to stochastic mFRET. An ensemble multicolour FRET model is introduced and used to extend multicolour barcoding to extreme FRET regimes, enabling in silico design of 580 barcode responses using common dyes and cytometer optics, and permitting fully automated decoding.